2019
DOI: 10.1038/s41598-019-45203-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of DNA methylation to the expression of FCGRT in human liver and myocardium

Abstract: FcRn mediates recycling and transcytosis of IgG and albumin in various cell types. The MHC-class-I-like protein of the FcRn heterodimer is encoded by FCGRT . Few determinants of variable FCGRT expression in humans have been identified so far. In this study, we investigated the presence of DNA methylation in regulatory regions of FCGRT in samples of human liver and myocardium tissue, and we examined the impact of FCGRT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It will be of interest to test whether the AICD fragment regulates the expression of FcRn. Points that merit further consideration are (1) whether the observed FCGRT - APP gene expression correlation extends to “inter-individual” comparisons involving various cell types and tissues from multiple donors, and (2) additional regulatory mechanisms that may impact FCGRT and FcRn expression in trisomic cells 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…It will be of interest to test whether the AICD fragment regulates the expression of FcRn. Points that merit further consideration are (1) whether the observed FCGRT - APP gene expression correlation extends to “inter-individual” comparisons involving various cell types and tissues from multiple donors, and (2) additional regulatory mechanisms that may impact FCGRT and FcRn expression in trisomic cells 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…25 Studies have linked DNAm to gene expression and disease processes, because DNAm can cause the gene to not be expressed (see Figure 3), and the removal of a methyl group can cause the gene to be expressed. [27][28][29] DNAm can be measured and compared using discrete methylation differential data. If comparing two cells, one from a disease process such as cancer and the other a control, the methylation of the exact same CpG site can be measured to determine the methylation level, which is reported as being hyper-methylated or hypo-methylated in the diseased cell.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Polymorphisms in intron 1 of FCGRT , which encodes for FcRn, affects FcRn abundance, mAb distribution between central and peripheral compartments, and the efficiency of intravenous Ig (IVIg) therapy [ 55 , 113 , 114 ]. Methylation-sensitive transcription factors Zbtb7a and Sp1 as well as the microRNAs hsa-miR-3181 and hsa-miR-3136-3p have been found to affect FCGRT expression [ 115 , 116 ]. Others have found that FcRn expression responds to immunological stimuli, with detailed investigations showing upregulation by tumor necrosis factor (TNF)-α through NF-κB and downregulation by interferon (IFN)-γ through JAK/STAT-1 [ 117 , 118 ].…”
Section: Fcrn Expression and Its Effects On Homeostatic Igg Distrimentioning
confidence: 99%